Prediction of temperature drop accompanying a given pressure drop for natural gas wellstreams - Bahadori, Alireza; Vuthaluru, Hari (Zagreb R, 2010)
Accurate prediction of the temperature drop accompanying a given pressure drop for the natural gas production systems is necessary in the effective design of natural gas production facilities. Current rigorous compositional models depend on many variables and require information about fluid composition. In this paper, a simple-to-use method which is easier than current available models, is presented to predict accurately the appropriate temperature drop accompanying a given pressure drop in natural gas production systems based on the black-oil model to get a quick approximate solution for the temperature drop of a natural gas streams in gas production systems. Considering the results, the new developed correlation is recommended for rapid estimation of temperature drops in gas production systems for pressures up to 45 MPa and pressure drops up to 25 MPa. The obtained results illustrate that good agreement is observed between the reported data and the values calculated using the new developed method. The average absolute deviation between reported data and the proposed correlation is around 4.6%. The proposed method appears to be superior owing to its accuracy and clear numerical background, wherein the relevant coefficients can be retuned quickly for various data.